PENDAPATAN DAN RISIKO USAHATANI CABAI DI KECAMATAN SUMBEREJO KABUPATEN TANGGAMUS - Nurul Mala; Fembriarti Erry Prasmatiwi; Wuryaningsih Dwi Sayekti (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This research aims to find out the comparison of income and the risk of chili pepper (Capsicum annum L.) farming and cayenne pepper (Capsicum Frutescens L.) farming.  The study was conducted in three villages at Sumberejo Sub-district of Tanggamus Regency.  This research used a survey method and respondents in this research were 30 chili pepper farmers and 30 cayenne pepper farmers.  The data analysis used is farm income analysis and risk analysis uses coefficient of variation. To find out the comparison of income and risk of farming was independent sample t-test. The results showed that the income of chili pepper farming was higher than that of cayenne pepper farming with the income of IDR119,047,409.08 per hectare and IDR49,579,450.49 per hectare. There is no significant difference between production risk and income from chili pepper and cayenne pepper farming. The price risk of chili pepper farming is higher than that of cayenne pepper.Key words: Chili farming, income, risk